Integrasi Pendidikan Akidah dan Matematika dalam Novel Guru Aini Karya Andrea Hirata - Muhammad Nasruddin; Toto Hermawan; Diyah Sari; Tri Ratna Herawati; Juhri Juhri (Intersections, 2021)
The main elements in Islam are faith, worship and morality. Actually all three are closely related to mathematics and its education for students. The novel Guru Aini is one of the books that seeks to integrate the understanding of the Islamic faith in learning mathematics by the mathematics teacher who is the main play. Through a literature review, it can be concluded that the educational values of Islamic faith contained in the novel Guru Aini (GA) by Andrea Hirata are: strengthening faith, trust, and belief. So what is meant by aqidah is a belief that pierces or is knotted in the heart. Tauhid or aqidah is a value that must be owned by an individual. The value of monotheism or aqidah is found in the form of limit and geometry concepts in the GA novel that are relevant to Tauhid Rububiyah.